2004
DOI: 10.5005/jcdp-5-4-23
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Various Oral Hygiene Strategies in Neuromusculary Disabled Individuals

Abstract: Background: This study aims to investigate the effect of various oral hygiene strategies on the symptoms of inflammation in neuromuscularly disabled patients and to define the optimum hygiene method.Methods: Fifty-nine neuromuscularly disabled participants, suffering from cerebral palsy, were randomly divided into five groups as follows: Group M: manual toothbrush (n=14), Group E: electrically powered toothbrush (n=9), Group MC: manual toothbrush and chlorhexidine gluconate (CHX) spray (n=13), Group EC: electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 40 publications
3
49
3
1
Order By: Relevance
“…in a study of healthy individuals aged between 18 and 67 years. Bozkurt et al . studied individuals with CP and found that the electric toothbrush was significantly superior to manual brushing, contrary to the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…in a study of healthy individuals aged between 18 and 67 years. Bozkurt et al . studied individuals with CP and found that the electric toothbrush was significantly superior to manual brushing, contrary to the results of the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…The reduction of biofilm observed in the present study was inferior to that found in studies with healthy individuals for all three brushing methods (Table ). The reduction of biofilm has been reported as lower in patients with motor disabilities, possibly due to the difficulties faced during brushing, which is similar to the findings of the present study. According to the Turesky modification Quigley–Hein index, the accumulation of up to 40% of biofilm on the dental surface can be considered acceptable and does not damage dental and periodontal structures.…”
Section: Discussionsupporting
confidence: 91%
“…Disregarding the PDD's heterogeneity as to the types and levels of their disabilities may obscure important information about subsets of this population with greater oral health needs. For example, gingival hyperplasia caused by certain antiseizure medications 24,25 and motor skill decrements among persons with cerebral palsy, 26 result in poorer oral hygiene and periodontal indices for special subsets of PDD.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, several important aspects, such as ability to maintain oral hygiene, caries, and periodontal conditions, have been discussed in individuals with cerebral palsy (8)(9)(10)(11)(12)(13). Nevertheless, the dental literature presents only a few studies evaluating the prevalence of dental trauma in children with different kinds of disabilities (14,15) or cerebral palsy.…”
mentioning
confidence: 99%